2022
DOI: 10.1007/s00404-021-06364-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian hormone and puberty development in girls and adolescents who underwent cancer treatment

Abstract: Background: High survival rate of children diagnosed with cancer has led to a growing population of women with premature ovarian failure (POF) due to chemotherapy and radiotherapy. The POF process occurs due to the disruption of the Hypothalamic-Pituitary and gonadal axis followed by the delay of puberty development. Evaluation of reproductive function in children with cancer is essential to determine the fertility preservation plan. This study aimed to describe reproductive function in children and adolescent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Most chemotherapy drugs cause reproductive toxicity in women, disrupting physiological homeostasis and adversely affecting many organs, especially in younger pa-tients [21]. Despite the fact that chemotherapeutics can be used to treat numerous types of cancer, ovarian toxicity in young female cancer patients must never be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Most chemotherapy drugs cause reproductive toxicity in women, disrupting physiological homeostasis and adversely affecting many organs, especially in younger pa-tients [21]. Despite the fact that chemotherapeutics can be used to treat numerous types of cancer, ovarian toxicity in young female cancer patients must never be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…The rats (n = 48) were randomly divided into four experimental groups (12 animals per group): 1 control group, 2 POF group, 3 10 mg/kg melatonin (MT10), and 4 20 mg/kg melatonin (MT20). The CTX-induced POF rats model was established according to the previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…1 About 60-80% of chemotherapy patients may experience POF. 2 CTX, as an alkylating agent commonly used in chemotherapy, induces severe ovarian damage and is a recognized risk of POF. 3,4 Studies have shown that CTX causes ovarian follicle failure by activating primal follicles and making them lose a lot.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Our previous study showed that, overall, chemotherapy can affect the ovarian reserve with regards to AMH level, altered menstrual regularity, as well as delayed pubertal development. 8 However, the correlation between cumulative dose of high-risk gonadotoxic agents such as cyclophosphamide and AMH levels has not been studied.…”
mentioning
confidence: 99%